Optimalisasi Strategi Digital dan Kolaborasi Hospitality Industry dalam Mempromosikan Little Tree Preschool - Puspitawati, Ni Made Dwi; Natalia, Kadek Novi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
In the digital era which is increasingly developing rapidly, conventional marketing strategies are no longer enough to reach a wide market. Little Tree Preschool as an early childhood education institution is required to adapt to more creative and relevant promotional strategies. The aim of the service is to integrate digital marketing strategies and collaboration with the hospitality industry. The methods used include (1) creating social media content as a means of promotion, (2) expanding collaboration with the hospitality industry, (3) providing learning experiences for students. The results achieved by communication strategies that have been proven effective in the service industry, such as email marketing and digital testimonials, Little Tree Preschool can increase brand awareness significantly. This approach not only benefits educational institutions, but also becomes an educational and applicable means of implementing the knowledge they have learned.